Factors influencing cyberbullying among young adults: Instagram case study - Oladimeji, Anthonia (Department of Information Systems, 2023)
Cyberbullying is one of the major problems of social networking sites, which has been known to have prolonged adverse psychological effects on social network users. Cyberbullying has been discussed a lot in the literature, but little research has been done on cyberbullying and its related factors. This study seeks to examine the factors influencing cyberbullying on Instagram among young adults. Instagram was chosen as a case study for the thesis because research shows that Instagram is the most preferred social networking site among the age cohort (18–30), who are popularly referred to as young adults. An extensive review of the literature was carried out, and six constructs (Instagram Usage, Vulnerability, Peer Pressure, Anonymity, and Instagram Features) were used to examine the influence of cyberbullying among young adults on Instagram. This study draws from the theory of routine activity theory (RAT), which is grounded on the postulation that criminal acts can be easily committed by any individual who has the opportunity. The researcher reviewed the process and deployed a methodological and concept-centric approach to create a comprehensive conceptual model that included key factors. This dissertation is different from most cyberbullying research in the sense that it reviews cyberbullying behaviours from the context in which they occur rather than the intent or motivation of the perpetrator. The model allowed a holistic examination of factors that influenced cyberbullying behaviours on Instagram. Using a survey methodology, over 201 Instagram users who are also students at the University of Cape Town completed an instrument measuring factor influencing cyberbullying. The researcher deployed Smart PLS, a statistical package for the social sciences, to test for reliability, validity and to analyse the entire dataset. The study critically examined the factors that influence cyberbullying among young adults. The results of this dissertation indicated that peer pressure and online vulnerability have a strong significance in cyberbullying behaviours. Surprisingly, Instagram usage had a weak correlation with cyberbullying behaviours. This study contributes significantly to the exciting research on cyberbullying as it helps identify the factors that contribute to cyberbullying behaviours. From this research, cyberbullying interventions or solutions can be accurately developed.